Nilai Religiusitas Dalam Novel “Mamu Zein” Karya Syeikh Dr. Mohammad Said Ramadhan Al-Buthi (Analisis Semiotika Charles Sanders Pierce) - Rahmat Hidayatullah (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
The material object in this research is the novel Mamu Zein by Sheikh Dr. Muhammad Said Ramadhan Al-Buthi. And the formal object is Charles Sanders Pierce's Theory of Semiotics. This study aims to find the value of religiosity in the novel Mamu Zein by Sheikh Buthi by using Charles Sanders Pierce's semiotic approach. The method in this study is a qualitative descriptive method. The results in this study are seven religious values ​​that appear in the novel Mamu Zein, as follows: 1. Recognition of the greatness of God, 2. Awareness that violence is not the only way to solve problems. 3. Awareness that God is the best place to ask and rely. 4. Prayer is a source of strength for Muslims. 5. Ridho to the fate experienced. 6. Strong Faith Gives Peace of Life. 7. Death is the Path of Encounter with God.